Networked Hyperlocal Activists: Digital Democracy and Engagement in Sub-Saharan Africa - Nikolaos Toumaras (Social Media + Society)
Digital activists play a pivotal role in fostering local democracy, civic participation, and social advocacy across sub-Saharan Africa. Using technological, social, and discursive layers of communication, these activists navigate complex socio-political environments to amplify marginalized voices and facilitate local governance dialogues. Platforms like WhatsApp and Facebook enable real-time communication, trust-building, and narrative framing within nano-media spaces, bridging online and offline interactions. Despite their transformative potential, significant challenges persist, including gender disparities, urban-rural divides, and platform-specific limitations that hinder inclusivity and scalability. The commodification of visibility on digital platforms and infrastructural inequities further constrain their impact. Addressing these barriers through improved digital infrastructure, digital literacy initiatives, and institutional support ensures the sustainability of hyperlocal nano-media efforts. These strategies showcase the interplay of local and digital approaches, advancing democracy and civic empowerment while navigating the unique complexities of African contexts.